(untitled) (Bangladesh Journal of Botany, 2023)
A field experiment was conducted to evaluate effects of deficit irrigation scheduling (DIS) and different Agri-Horti System (AHS) on nutrient uptake, quality and fertilizer productivity of Indian mustard under sandy loam soil. Results revealed that among different levels of irrigation scheduling 0.6 IW (irrigation water)/ Cumulative pan evaporation (CPE) ratio resulted in higher amount of total N, P, K and S uptake which remained significantly superior over 0.4 IW/CPE and rainfed treatments. Among different AHS, Moringa (Moringa oleifera L.) based AHS exhibited significantly higher nutrient uptake, quality and fertilizer productivity followed by phalsa (Grewia asiatica L.), karonda (Carissa carandas L.), Indian gooseberry (Phyllanthus emblica L.) and guava (Psidium guajava L.) based AHS. Results revealed that Indian mustard could be suitably irrigated with 0.6 IW/CPE ratio to achieve higher nutrient uptake, quality and fertilizer productivity under moringa based AHS. Bangladesh J. Bot. 52(3): 821-827, 2023 (September)